Design of Filing System for police investigation report on the Forensic Document Unit of POLRI Forensic Laboratory Center - Rochani Ani; Saeful Lukman; Bheta Agus Wardijono (International Journal of Science and Engineering, 2019)
The Archiving system of Official Report of Inspection that runs on the Forensic Document Unit of POLRI Forensic Laboratory is particularly inefficient and effective as it still implements conventional filing systems. The recording of Official Report Documents is only in the general ledger. Based on these problems, the authors formulated "How to create an archiving information system that is expected to accelerate the process of searching, packing, storing records in a safe place". The objective of the research is to produce Information Archiving Information Archive Information System on Forensic Document Forensic Unit of POLRI Forensic Laboratory Center for better, faster, accurate and efficient.With this system archive data processing  archives more centralized and can help search and printing files / data quickly without having to search the archives are stacked, can avoid the loss of original archives. This is due to a scan of the original file that can be seen on this system. Based on the results of the test show that the system built successfully build the police investigation report Archive database. Thus it can be concluded that Official Report of Inspection Archiving System has been successful and ready to be implemented.